Cannabimimetic effects of abused indazole-carboxamide synthetic cannabinoid receptor agonists AB-PINACA, 5F-AB-PINACA and 5F-ADB-PINACA in mice: Tolerance, dependence and withdrawal. (1st July 2022) - Wilson, Catheryn D.; Hiranita, Takato; Fantegrossi, William E.
Abstract: Background: Chronic abuse of synthetic cannabinoid receptor agonists (SCRAs), known as "K2″ or "Spice", threatens public health and safety. Recently, SCRAs of the indazole-carboxamide structural class have become more prevalent. Preclinical studies investigating the tolerance and dependence potentially involved in chronic SCRA abuse is limited. The present study determined the in vivo effects of chronic exposure to indazole-carboxamide SCRAs, AB-PINACA, 5F-AB-PINACA and 5F-ADB-PINACA compared to the first-generation SCRA, JWH-018. Methods: Adult male C57Bl/6 mice were used for dose-effect determinations of hypothermic effects. Adult male NIH Swiss mice were used in biotelemetry studies to assess tolerance to hypothermic effects following repeated SCRA administration over 5 consecutive days, and to determine the role of Phase I drug metabolism via acute CYP450 inhibition in the presence of 1-ABT, a nonspecific CYP450 inhibitor. SCRA dependence was determined in adult male NIH Swiss mice via assessment of rimonabant-precipitated observable sign of withdrawal (i.e., front paw tremors). Results : All SCRAs elicited dose-dependent hypothermia mediated through cannabinoid CB1 receptors (CB1Rs). 1-ABT increased duration of hypothermia for all SCRAs tested, and increased the magnitude of hypothermia for all SCRAs except 5F-ADB-PINACA. Upon repeated administration, tolerance to hypothermic effects of AB-PINACA, 5F-AB-PINACA and 5F-ADB-PINACA was much less than that of JWH-018. Similarly, rimonabant-precipitated front paw tremors were much less frequent in mice treated with 5F-AB-PINACA and 5F-ADB-PINACA than in mice treated with JWH-018. Conclusions: These findings suggest a decreased potential for tolerance and withdrawal among indazole-carboxamide SCRAs, and may imply structural class-dependent profiles of in vivo effects among SCRAs. Highlights: AB-PINACA, 5F-AB-PINACA and 5F-ADB-PINACA elicit CB1R-mediated hypothermic effects. Inhibition of CYP450 enzymes enhances these hypothermic effects. Less tolerance develops to hypothermic effects of indazole-carboxamides than to JWH-018. Compared to JWH-018, reduced dependence develops to 5F-AB-PINACA and 5F-ADB-PINACA.